2021
DOI: 10.14202/vetworld.2021.1511-1528
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphometric changes in the small intestine during hot and cold exposure in thermally manipulated broiler chickens

Abstract: Background and Aim: Thermal stress (hot or cold) is one of many environmental stressors that severely affects the health of broiler chickens. One negative effect of thermal stress is the disruption of the intestinal barrier function in broiler chickens. This study aimed to evaluate the effect of thermal manipulation (TM) on the small intestine in terms of histomorphometry as well as junctional, heat-shock, and immune response gene expression during post-hatch exposure to thermal stress. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Generally, higher VH and shorter CD indicate better intestinal development [ 30 ]. Previous studies have shown that cold stress at 2–8 °C can decrease VH, CD, and VH / CD in the intestines of broiler chicken [ 31 ]. In the study of piglets, it was also found that cold stress can reduce VH and VH / CD in the duodenum of piglets, and an increase in CD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, higher VH and shorter CD indicate better intestinal development [ 30 ]. Previous studies have shown that cold stress at 2–8 °C can decrease VH, CD, and VH / CD in the intestines of broiler chicken [ 31 ]. In the study of piglets, it was also found that cold stress can reduce VH and VH / CD in the duodenum of piglets, and an increase in CD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific alterations have been reported to disrupt Hsps expression between intestinal segments (duodenum, ileum, and jejunum) of poultry subjected to HS conditions [ 64 , 65 ]. Khaleel et al [ 66 ] and Al-Zghoul and Saleh et al [ 55 ] reported that thermally manipulated broiler chickens showed an altered post-hatch response to chronic HS in the jejunal mucosae by reducing the expression of Hsp70 and Hsf1 and 3. Similarly, embryonic TM from day 11 of incubation until hatching improved intestinal integrity and reduced Hsp70 expressions [ 67 ].…”
Section: Effect Of Thermal Manipulation On the Regulation Of Heat Sho...mentioning
confidence: 99%
“…Similarly, chickens under heat stress conditions show decreased jejunal mass, suggesting that high temperatures further reduce intestinal mass and depress enterocyte proliferation and growth (Garriga et al, 2006;Uni et al 2001, Sughiarto et al, 2017. Khaleel et al (2021) observed that broilers exposed to different temperature conditions before hatching, had different values in the length of the villi to depth of the jejunum crypts ratio (VH:CD) in conditions of cold or heat stress for more than 4 days. These data demonstrate that variation in temperature changes intestine morphology.…”
Section: Discussionmentioning
confidence: 99%